Preparation and evaluation of novel self-dispersing lipid formulation of nevirapine for oral delivery - Gopalapura Bellaiah Preethi, Hagalavadi Nanjappa Shivakumar, Madalli Ravi Kumar (Journal of Applied Pharmaceutical Science, 2022)
Nevirapine, a non-nucleoside reverse transcriptase inhibitor, exhibits pH-dependent solubility resulting in poor dissolution limiting its absorption. In the present study, an attempt is made to prepare a self-dispersing lipid formulation (SDLF) involving the novel combination of two drug solubility enhancing strategies, i.e., self-emulsifying system (SES) and solid dispersion (SD). Nevirapine-SES (NV-SES) consisting of an ideal ratio of oleic acid (oil), Cremophor RH 40 (surfactant), and Transcutol (co-surfactant) exhibited good emulsifying properties with maximum drug loading. The NV-SES developed was mixed with an equal quantity of nevirapine: gelucire 50/13 solid dispersion [Nevirapine Solid Dispersion (NV-SD)] to get a novel nevirapine SDLF (NV-SDLF). The NV-SDLF was characterized for its zeta potential, polydispersity index, and particle size, and the results obtained were found to be satisfactory. NV-SDLF was adsorbed on carrier neuciline U2 to get solid NV-SDLF, and solid-state characterization using Differential Scanning Calorimetry (DSC) and Powder X-Ray Diffraction (PXRD) indicated the amorphous nature of the drug in NV-SDLF. The in-vitro drug release of the NV-SDLF was found to be 87.2% ± 0.96% in comparison with nevirapine 28.8% ± 1.02%. In-vivo pharmacokinetic performance of solid NV-SDLF and pure drug suspension was carried out in rats, and a significant two-fold increase (p < 0.05) in area under the curve (AUC) of solid NV-SDLF was observed with respect to nevirapine AUC. Thus, the in-vitro and in-vivo results confirmed that the combined strategies of SES and SD in the formulation of solid NV-SDLF were found to enhance the bioavailability of nevirapine, which could be a promising novel drug delivery system in the management of Acquired Immune Deficiency Syndrome (AIDS).
Keywords: Nevirapine, Self emulsifying system, Lipid based solid dispersion, Lipid based drug delivery, Gelucire 50/13